Forage potential of Erythrina abyssinica: Intake, digestibility and growth rates for stall-fed sheep and goats in southern Ethiopia - Larbi, Asamoah; Thomas, D.; Hanson, Jean (Springer, 1993)
Feeding value of Erythrina abyssinica leaves were evaluated with native sheep and goats at Soddo, southern Ethiopia in a 21-day digestibility and 80- day growth trial. In the digestibility trial, wilted leaves of E. abyssinica were fed add libitum, while in the growth trial, animals were offered a basal diet of purpureum with three levels (0,500,100 g/head/day) of E. abyssinica leaf. No significant differences were found between sheep and goats in voluntary intakes and digestibilities of organic matter, nitrogen and neutral detergent fiber. Supplementing a basal diet of purpureum with increasing levels of E. abyssinica leaves resulted in reduced intake of purpureum, but increased total organic matter intake in both species. Liveweight gains of sheep and goats increased linearly with increasing levels of E. abyssinica leaf supplementaiton. Sheep gained weight faster than goats. Based on the results it was concluded that E. abyssinica has high forage potential and can effectively serve as a cheap source of protein supplement for low quality diets during the dry season for resource-poor farmers with stall-fed sheep and goats.